2003
DOI: 10.1046/j.1365-2303.2003.00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology of follicular variant of papillary carcinoma of thyroid

Abstract: In this retrospective study, we tried to ascertain the fine needle aspiration cytology (FNAC) features of six histopathologically proven cases of the follicular variant of papillary carcinoma of thyroid (FVPCT). These proven cases were diagnosed from 1998-2000. May-Grunwald-Giemsa and haematoxylin & eosin stained FNAC smears were studied independently by two observers (MP and PD) for detailed cytological features. A comparison of the cytological features was undertaken with those reported in the literature. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 5 publications
1
25
1
Order By: Relevance
“…It has been reported to cause a large proportion of false-negative results in thyroid FNA, with sensitivities ranging from 9 to 37%, and it has been shown that its cytological findings more likely fall into the lower-risk category in comparison to the classical variant [7,9,11,13,14,15]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to cause a large proportion of false-negative results in thyroid FNA, with sensitivities ranging from 9 to 37%, and it has been shown that its cytological findings more likely fall into the lower-risk category in comparison to the classical variant [7,9,11,13,14,15]. …”
Section: Discussionmentioning
confidence: 99%
“…Unlike papillary thyroid carcinoma, preoperative diagnosis of follicular thyroid carcinoma with FNAC is difficult [17,19]. Capsule and vascular invasion are the main characteristic differences between thyroid follicular adenoma and carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…According to Powari et al, [17] FVPTC should be considered in the diagnosis if the smears show high cellularity, syncytial clusters and follicular arrangement and thick colloid. Shih SR et al, [15] concluded in their study that it was difficult to differentiate FVPTC from classic PTC in FNAC and when follicular structures were seen in smears, careful search for nuclear features should be done.…”
Section: Discussionmentioning
confidence: 99%